The New Poor of Contemporary Colombia : Armed Conflict And Impoverishment of Internally Displaced Persons (2005)
Today, the Colombian humanitarian crisis of internally displaced persons (IDPs) is one of the mainfactors contributing to the growing number of people who rapidly become extremely poor, and floodinto “belts of misery" in, and around, major cities. This paper examines the impact of the internal armed conflict in contemporary Colombia on the well-being of IDPs, through analysis of causal connections between the internal armed conflict, internal displacement and the process of impoverishment of IDPs.In this research paper we provide a historical overview of the development of the internal displacement phenomenon in Colombia and evaluate changes in various socio-demographic characteristics of IDPs due to the internal displacement during the 1990s.